Structural Equation Modeling of Pain Management Based on Rumination and Positive and Negative Emotional Regulation Mediating Vitality in Women With Breast Cancer - Fatemeh Givi; Farahnaz Meschi; Masoumeh Zhian Bagheri; Dariush Farhood (Zanjan University of Medical Sciences and Health Services, 2022)
Background: Pain management in patients with breast cancer is possible when it is considered in connection with emotional regulation. In patients with emotional problems and anxiety, emotion regulation can be good predictors for controlling their negative emotions. Objectives: This study aimed to explain the pain management model based on rumination and positive and negative emotional regulation mediating vitality in women with breast cancer. Methods: The research method was descriptive correlation modeling (structural equations). Participants in this study were women with breast cancer referred to all medical centers (hospitals and private and public clinics) in Tehran, of whom 273 were randomly selected. To measure the research variables, rumination response questionnaires, positive and negative emotional regulation, and vitality and pain management scales were used. SPSS 22 and LISREL 8.80 software were used to perform Spearman's correlation coefficient test and path analysis for data analysis. Results: The results showed that the indirect effect of positive emotional regulation was significant on vitality-mediated catastrophe (β=-0.07, P≤0.05). Also, the indirect effect of negative emotional regulation was significant on vitality-mediated catastrophe (β=0.11, P≤0.05). Conclusion: It can be concluded that the pain management model based on rumination and positive and negative emotional regulation with vitality mediation in women with breast cancer has sufficient fitness.